DEVELOPMENT OF ARTICULATE STORYLINE INTERACTIVE MEDIA BASED ON PROBLEM BASED LEARNING IN SCIENCE LEARNING IN CLASS - Muthiah Wandani, Frisya Alvita; Yarmi, Gusti; Supriatna, A.R (Educational Technology Journal, 2024)
This research and development aims to deliver products, determine the feasibility, and effectiveness of the interactive media Articulate Storyline based on Problem-Based Learning in science learning for grade IV elementary school students. This research uses the ADDIE development model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluate. Product validation trials were carried out by involving material experts, media experts, linguists, and fourth grade students of SDIT Cendekia Islamic School Bekasi City. Information collection was obtained from observations, interviews with fourth grade teachers, and questionnaires. The results of the material expert validation were 95%, media experts 96.6%, and linguists 97.9%. Thus obtaining the average overall result of the experts validation is 96.5%. The results of the one to one product trial were 82.1%, small group 88.5%, and field test 92.5%. As well as getting an increase in learning outcomes from the pre-test 72.76 and post-test 93.72. Thus, this shows that the interactive media Articulate Storyline based on problem-based learning is feasible and effective to be used as an alternative or additional learning media for grade IV elementary school students.